Correlating the effect of dopant type (Al, Ga, Ta) on the mechanical and electrical properties of hot-pressed Li-garnet electrolyte. Issue 5 (May 2020) - Han, Gigap; Kinzer, Bryan; Garcia-Mendez, Regina; Choe, Heeman; Wolfenstine, Jeff; Sakamoto, Jeff
Abstract: The effect of cubic-phase stabilizing dopant (Al, Ga, Ta) on the mechanical and electrochemical properties of Li garnet solid electrolyte was studied. Dense Li6.25 La3 Al0.25 Zr2 O12, Li6.50 La3 Ta0.50 Zr1.5 O12, Li6.25 La3 Ga0.25 Zr2 O12 were prepared by conventional solid-state synthesis of powder and densified using hot pressing. Ga-LLZO exhibited the highest fracture stress (∼143 MPa), fracture toughness (∼1.22 MPa m 1/2 ) and total conductivity (∼1 mS/cm) of the three materials; however, the bulk conductivity was about 1.5 mS/cm. We believe that the weak grain-boundaries, as evidenced by a predominately intergranular fracture, correlates with a relatively high grain-boundary impedance, thus reducing the value of the total conductivity by about 30 % lower than that for the bulk. Based on the combined mechanical and electrical properties, overall, Li6.25 La3 Ga0.25 Zr2 O12 exhibits the most favorable combination of some of the most salient properties of the three dopants. We believe the results of this study will facilitate the commercialization of Li metal batteries using Li-garnet ceramic electrolyte.